Nigeria [in Strategies and priorities for African agriculture] - Diao, Xinshen; Nwafor, Manson; Alpuerto, Vida; Akramov, Kamiljon T.; Rhoe, Valerie; Salau, Sheu (International Food Policy Research Institute, 2012)
Nigeria, whose export earnings are heavily oil dependent, has experienced rapid economic growth in recent years. In 1990–99 the economy grew at 2.6–3.0 percent annually, whereas the annual gross domestic product (GDP) growth rate rose to 7.3 percent during 2000–07 (Nigeria, NBS 2007a). Notably, the agricultural sector has been the key driver of the economy, growing at 6.3 percent and contributing 42 percent to the country’s total GDP in 2008. Hence, despite the high dependence of government revenues and national export earnings on the oil sector, the agricultural sector remains the country’s mainstay (Sanyal and Babu 2010). Furthermore, because agriculture is the largest employer among all sectors (70 percent of the labor force) (Nigeria, NBS 2006) and labor is the main (and sometimes only) asset for the poor (Agenor Izquierdo, and Fofack 2003), the agricultural sector has the greatest potential for reducing poverty.